2018
DOI: 10.1089/dia.2018.0252
|View full text |Cite
|
Sign up to set email alerts
|

Switching from Flash Glucose Monitoring to Continuous Glucose Monitoring on Hypoglycemia in Adults with Type 1 Diabetes at High Hypoglycemia Risk: The Extension Phase of the I HART CGM Study

Abstract: Background: The I HART CGM study showed that real-time continuous glucose monitoring (RT-CGM) has greater beneficial impact on hypoglycemia than intermittent flash glucose monitoring (flash) in adults with type 1 diabetes (T1D) at high risk. The impact of continuing RT-CGM or switching from flash to RT-CGM for another 8 weeks was then evaluated.Methods: Prospective randomized parallel group study with an extension phase. After a 2-week run-in with blinded CGM, participants were randomized to either RT-CGM or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 18 publications
2
98
1
Order By: Relevance
“…A pilot randomized controlled study demonstrated that rtCGM but not isCGM therapy reduced exposure to hypoglycemia in patients with T1D and impaired awareness of hypoglycemia, suggesting that threshold alerts unique to rtCGM systems are important for hypoglycemia avoidance. 23,24 The current data demonstrate that the incorporation of a predictive low glucose alert into a G6 CGM system further diminishes hypoglycemia exposure, significantly reducing hypoglycemia relative to a CGM system without the predictive alert, independent of threshold alert setting. It is not surprising that users with a threshold alert setting of 80 mg/dL tended to spend less time in hypoglycemia overall compared with those with a threshold alert setting of 70 mg/dL; having a low threshold alert of 80 mg/dL provides more advanced warning to intervene before hypoglycemia.…”
Section: Discussionmentioning
confidence: 71%
“…A pilot randomized controlled study demonstrated that rtCGM but not isCGM therapy reduced exposure to hypoglycemia in patients with T1D and impaired awareness of hypoglycemia, suggesting that threshold alerts unique to rtCGM systems are important for hypoglycemia avoidance. 23,24 The current data demonstrate that the incorporation of a predictive low glucose alert into a G6 CGM system further diminishes hypoglycemia exposure, significantly reducing hypoglycemia relative to a CGM system without the predictive alert, independent of threshold alert setting. It is not surprising that users with a threshold alert setting of 80 mg/dL tended to spend less time in hypoglycemia overall compared with those with a threshold alert setting of 70 mg/dL; having a low threshold alert of 80 mg/dL provides more advanced warning to intervene before hypoglycemia.…”
Section: Discussionmentioning
confidence: 71%
“…The study showed that use of rtCGM more effectively reduces time spent in hypoglycemia in T1D adults with impaired hypoglycemia awareness compared with isCGM use. An extension of the IHART-CGM trial showed similar findings ( 12 ). However, there are no comparative studies regarding use of these devices during periods of physical activity or within unselected patient populations.…”
Section: Introductionmentioning
confidence: 63%
“…Change from baseline in each study phase was compared between the two interventions. On the basis of previous studies ( 8 , 12 , 16 ), we estimated 5% improvement in time below range (TBR) (<3.9 mmol/L [<70 mg/dL]) in the rtCGM group with an SD of 9% for the paired difference between study phases. Using these criteria, 28 subjects in each group (56 in total) were required to achieve the desired 80% power and an α level of 0.05 (two-tailed t test).…”
Section: Methodsmentioning
confidence: 99%
“…The study demonstrated, among others, a significant reduction in time spent in clinically relevant hypoglycemia (<3.3 mmol/L, 59 mg/dL) . Furthermore, an extension of this study showed that patients who switched from FGM to RT‐CGM further diminished hypoglycemic burden and improved time in range . However, reservations were made about the study's design concerning different mean absolute relative difference of the systems and our results add to uncertainty.…”
Section: Discussionmentioning
confidence: 60%